“Non-Toxic” Proteins of the Botulinum Toxin Complex Exert In-vivo Toxicity - Miyashita, Shin-Ichiro (Sci Rep, 2016)
The botulinum neurotoxin (BoNT) causes muscle paralysis and is the most potent toxin in nature. BoNT is associated with a complex of auxiliary “Non-Toxic” proteins, which constitute a large-sized toxin complex (L-TC). However, here we report that the “Non-Toxic” complex of serotype D botulinum L-TC, when administered to rats, exerts in-vivo toxicity on small-intestinal villi. Moreover, Serotype C and D of the “Non-Toxic” complex, but not BoNT, induced vacuole-formation in a rat intestinal epithelial cell line (IEC-6), resulting in cell death. Our results suggest that the vacuole was formed in a manner distinct from the mechanism by which Helicobacter pylori vacuolating toxin (VacA) and Vibrio cholerae haemolysin induce vacuolation. We therefore hypothesise that the serotype C and D botulinum toxin complex is a functional hybrid of the neurotoxin and vacuolating toxin (VT) which arose from horizontal gene transfer from an ancestral BoNT-producing bacterium to a hypothetical VT-producing bacterium.